Immunopathology and Immunomodulation - Metodiev, Krassimir (IntechOpen, 2015)
This book is a continuation of the efforts of InTech to expand the scientific know-how in the field of immunopathology and bring valuable updated information to medical professionals and researchers. It consists of chapters related to various approaches to investigate the unique role of the immune system in response to different clinical disorders. The international team of authors is the bonus of the book, reflecting the rapid development of immunology and new achievements in medical science. We firmly hope that the book will be an excellent manual and guideline for people dealing with biology, microbiology, immunology, virology, pharmacology, general and dental medicine, and health care, from students and postdocs to high-level specialists and university professors.